2018
DOI: 10.1038/s41598-018-23275-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a dyadic motor plan in joint action

Abstract: What mechanisms distinguish interactive from non-interactive actions? To answer this question we tested participants while they took turns playing music with a virtual partner: in the interactive joint action condition, the participants played a melody together with their partner by grasping (C note) or pressing (G note) a cube-shaped instrument, alternating in playing one note each. In the non-interactive control condition, players’ behavior was not guided by a shared melody, so that the partner’s actions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
69
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 49 publications
18
69
1
Order By: Relevance
“…Furthermore, the analysis of temporal delays between neural activity and the behavioral parameters, measured for the own and the other actions, showed that the time lags were mostly negatives for both canonical action-related and joint-action cell populations, supporting the view of a corepresentation of the two behaviors based on feedforward processes. This agrees with the dyadic motor plan view of Sacheli et al (2018), which demonstrates how a successful joint-performance relies on the active prediction of the partner's action, rather than on its passive imitation or observation. Our data offer an experimental evidence for a single-unit mechanism subtending intersubject motor coordination, which is reminiscent of a predictive coding (Rao and Ballard, 1999;Friston, 2005), proposed in humans to automatically anticipate others' mental states (Thornton et al, 2019).…”
Section: Joint-action Cells In Primate Premotor Cortexsupporting
confidence: 86%
“…Furthermore, the analysis of temporal delays between neural activity and the behavioral parameters, measured for the own and the other actions, showed that the time lags were mostly negatives for both canonical action-related and joint-action cell populations, supporting the view of a corepresentation of the two behaviors based on feedforward processes. This agrees with the dyadic motor plan view of Sacheli et al (2018), which demonstrates how a successful joint-performance relies on the active prediction of the partner's action, rather than on its passive imitation or observation. Our data offer an experimental evidence for a single-unit mechanism subtending intersubject motor coordination, which is reminiscent of a predictive coding (Rao and Ballard, 1999;Friston, 2005), proposed in humans to automatically anticipate others' mental states (Thornton et al, 2019).…”
Section: Joint-action Cells In Primate Premotor Cortexsupporting
confidence: 86%
“…The results from the group which performed the Joint Action Goal Condition last indicate that a joint action goal representation may, as we predicted, reduce visuomotor interference effects arising from the observation of a physically incongruent action. These results build upon earlier research indicating that the visuomotor interference effects arising from the perception of a virtual partner's physically incongruent movement can be reduced when two physically incongruent movements are represented as complementary contributions to a joint action goal 14,20 . Our results extend this research by suggesting that a joint action goal representation can reduce visuomotor interference effects even when agents must detect a joint action partner's physically incongruent movement while simultaneously producing actions that are contingently related to these.…”
Section: Discussionsupporting
confidence: 85%
“…Sacheli et al's proposed answer is that the representation of a joint action goal enables joint action partners to integrate representations of their own and their partner's actions within a single dyadic (multi-person) motor plan 14 . As they put it, this dyadic motor plan enables them to select appropriate responses to their partner's actions on the basis of their predicted outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interactive gestures may in fact be processed based on a sensorimotor coding that maps the representation of the observed action onto an interactive script that triggers a complementary response. This would imply that when observers perceive a gesture that is a component of hand-shaking, a hand-shaking script would be activated in the sensorimotor system of the observer and facilitate the performance of the complementary hand shaking action (see [13,14,15,16,17,18,19]). In other words, the perception of interactive gestures might entail social affordances.…”
Section: Introductionmentioning
confidence: 99%